Attitude, behaviour and awareness of Turkish women concerning breast cancer - (:unkn) unknown (My University, 2002)
Objective: Over half a million women develop breast cancer every year. Despite rising incidence, survival rates can be increased by public health efforts to promote routine self-examination and regular mammograms in order to detect cancer at an early stage. The objective of this study is to determine women's awareness, practice and attitudes towards breast cancer and to be a guide for education programmes aimed at making women more informed and enabling them to act with more knowledge. Method: Questionnaires, composed of 26 questions, were conducted among 375 women living in different areas of Istanbul. Each completed questionnaire was analysed and graded according to participant's level of information concerning breast cancer. Results: The level of information has a direct relationship with age, education and family income. Those with a good level of information were found to be: 57,6% of women above 51 years of age; 60% of all women who stated an income of above one billion TL, and; 62,2% of women graduated from a university. Conclusion: Health education on breast cancer should be provided especially to those with a poor level of information.
Keywords: Attitude; Awareness; Breast cancer; Practice